HUBUNGAN BURNOUT AKADEMIK DAN INFERIORITY FEELING TERHADAP KECURANGAN AKADEMIK PADA MAHASISWA - Fata Nabila, Aula; Chorynia Ruby, Arcivid (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study was conducted to determine the relationship between academic burnout and feelings of inferiority toward academic cheating among students. The study used a quantitative approach with a correlational method. This study involved 86 respondents selected using purposive sampling techniques. The instruments used in this study were an academic cheating scale, an academic burnout scale, and an inferiority feeling scale. The correlation coefficient between the three variables was 0.470 with a p-value of 0.000 (p < 0.01) and an effective contribution of 22.1%. This indicates a highly significant relationship between academic burnout and feelings of inferiority with academic dishonesty. The hypothesis test showed a highly significant positive relationship between academic burnout and academic dishonesty with a correlation coefficient of 0.438 and a p-value of 0.000 (p < 0.01). The next hypothesis test also showed a highly significant positive relationship between feelings of inferiority and academic dishonesty, with a correlation coefficient of 0.401 and a p-value of 0.000 (p < 0.01). The conclusion drawn from the research results is that there is a highly significant positive relationship between the three variables, both between academic burnout and academic cheating and between feelings of inferiority and academic cheating.